Integrated Systems, Design and Technology 2010 Knowledge Transfer in New Technologies - Fathi, Madjid; Holland, Alexander; Ansari, Fazel; Weber, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Knowledge creation and technological experiences resulting from modern pro-duction life cycles are definitely the most Economical and important intellectual capitals in the current manufacturing endeavors. These are also the basis for enabling industrial competition through managing and identifying organizational and product related needs and opportunities; eg. health care systems society needs clean environment, sustainable production life cycles needs flexible approachable design and engineering of materials whilst val-uable materials are needed for renewable energies and the production of fuel-cells. Integration of components, design of structures and managing knowledge inherent in engineering is a difficult and complex endeavor. A wide range of ad-vanced technologies such as smart materials and their approaches in alternative energy have to be invoked in providing assistance for knowledge requirements ranging from acquisition, modeling, (re)using, retrieving, sharing, publishing and maintaining of knowledge. Integration, Design and management with regards to knowledge management originates at least on three roots.
Part 1 Advanced Materials and Design -- Part 2 Advanced Energy Utilization - Fuel Cell -- Part 3 Computational and Intelligent Systems Engineering.
Keywords: Engineering; Engineering design; Electric engineering; Engineering; Engineering Design; Energy Technology; Computational Intelligence